Comprehensive dynamic modeling, simulation, and validation for an industrial boiler incident investigation. Issue 4 (19th February 2019) - Taimoor, Aqeel Ahmad; Alghamdi, Mohammad Moghram; Farooqi, Muhammad Omer; Siddiqui, Muhammad Ehtisham; Zain‐ul‐Abdein, Muhammad; Saleem, Waqas; Ijaz, Hassan; Ali, Arshid M.
Abstract : Industrial boilers simulation can serve number of purposes like training, optimization, HAZOP studies, and incident investigation. Simulation including trip logics, interlockings, safety devices, start‐up and shutdown procedure is presented in this work. Simulation is directly accomplished in dynamic mode to benefit from the holdup approach to avoid anomalies because of recycling. The industrial DCS/PLC diagrams are replicated to imitate the boiler‐integrated behavior. Trip logics, start‐up and shutdown procedures are programmed using event scheduler . The inbuilt pressure relief module validates the simulated PSVs and rupture disc capacities. The model is then verified at three stages including 'steady state' achievement in dynamic mode, controller validation by start‐up and shut down procedures and finally by direct industrial data under deviant conditions. Where an unfortunate event is a concern, it also provides an opportunity to ponder and to evolve at various levels. Operational simulation of any such incident may help in getting a deep insight and thus to take accurate countermeasures. One such attempt is done in this work. A boiler accident has been reported. The complete response of the controllers and interlockings/trip system is imitated. The obtained results were compared with the chain of events that took place. © 2019 American Institute of Chemical Engineers Process Saf Prog: e12040 2019